Atractylenolide-1 Targets FLT3 to Regulate PI3K/AKT/HIF1-α Pathway to Inhibit Osteogenic Differentiation of Human Valve Interstitial Cells - Wang, Jie; Zhang, Penghua; Zhang, Jing; Ma, Zhaohui; Tian, Xingqin; Liu, Yan; Lv, Guanghui; Qu, Linghang (Frontiers in Pharmacology, 2022)
Atractylenolide-1 (AT-1), a natural active ingredient extracted from Atractylodes macrocephala, has been proved to have good anti-inflammatory and anti fibrosis effects. Osteogenic changes induced by inflammation of valve interstitial cells (VIC) plays a key role in the development of calcified aortic valve disease (CAVD).This study aimed to investigate the anti osteogenic differentiation of AT-1 in human valve interstitial cells.Human VICs was exposed to osteogenic induction medium (OM) containing AT-1 for further cell viability, osteogenic gene and protein expression and anti calcification test. mRNA transcriptome sequencing was used to find differential genes and pathways regulated by AT-1. Western blotting is used to verify the enrichment pathway, PPI analysis is used to find drug targets, and finally molecular docking and inhibitors are used to verify drug targets.No significant AT-1 cytotoxicity was seen in the VICs at 20 μM. The addition of AT-1 to OM prevented calcified nodule accumulation, and a decrease in the gene/protein expression levels of ALP, RUNX2 was observed. Atractylenolide-1 can target the FLT3 protein and inhibit the phosphorylation of FLT3, thereby blocking the activation of the PI3K/AKT pathway, reducing the production of HIF1-α, thereby inhibiting the osteogenic differentiation of valve interstitial cells. AT-1 is a potential drug for the treatment of calcified aortic valve disease.